Analysis of Generation Z Consumer Decisions in Using QRIS as a Digital Payment System - Putri, Pasya Adinda; Zibarani, Virgi Baker Awan; Lysa, Gisheila Hana; Ramadhan, Marshall; Zakiah, Rizka (Jurnal Ekonomi, Manajemen, dan Bisnis, 2024)
Digital transformation has reshaped consumer behavior in financial transactions, particularly among generation Z, who are highly adaptive to technology. This study aims to analyze generation Z consumer decisions in using QRIS as a digital payment system. A descriptive qualitative approach was employed, using online open-ended questionnaires distributed to 227 respondents aged 13–28 years. Thematic analysis was conducted to identify factors influencing QRIS usage decisions. The results indicate that ease of access, transaction speed, and perceived security are dominant factors in the adoption of QRIS, while social influence also plays a significant role among generation Z users. This study highlights the importance of enhancing digital literacy and strengthening consumer trust in technology-based payment services